2015
DOI: 10.1111/agec.12202
|View full text |Cite
|
Sign up to set email alerts
|

Examining gender inequalities in land rights indicators in Asia

Abstract: A broad consensus has emerged that strengthening women's property rights is crucial for reducing poverty and achieving equitable growth. Despite its importance, few nationally representative data exist on women's property rights in Asia, hindering formulation of appropriate policies to reduce gender gaps in land rights. This paper reviews existing micro-level, large sample data on men's and women's control of land, using this information to assess gaps in land rights. Utilizing nationally representative indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 19 publications
2
54
0
Order By: Relevance
“…First, husband's, wife's or jointly owned assets may not be equally important to household livelihoods, and it is more likely that the household (acting collectively) would decide to preserve that asset that is most important to generating the household's incomes. In some societies, this might be a large asset such as land, which tends to be owned by men, given documented gender inequalities in landownership (Doss, Kovarik, Peterman, Quisumbing, & van den Bold, ; Kieran, Sproule, Doss, Quisumbing, & Kim, ). Second, even for the same type of asset, differences in bargaining power within the household may imply that the person with less bargaining power has a higher probability of losing that asset.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…First, husband's, wife's or jointly owned assets may not be equally important to household livelihoods, and it is more likely that the household (acting collectively) would decide to preserve that asset that is most important to generating the household's incomes. In some societies, this might be a large asset such as land, which tends to be owned by men, given documented gender inequalities in landownership (Doss, Kovarik, Peterman, Quisumbing, & van den Bold, ; Kieran, Sproule, Doss, Quisumbing, & Kim, ). Second, even for the same type of asset, differences in bargaining power within the household may imply that the person with less bargaining power has a higher probability of losing that asset.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Kieran et al (2015) reported that in India almost 90% of agricultural landholders are men. According to Harper et al (2014), one way of enabling women to make decisions related to land use is to focus on ensuring women's ability to own (and inherit) land and other assets.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…This suggests that the design of such reforms needs to be more water tight in order to ensure that the target beneficiaries (women, in this case) are able to benefit as expected. While land ownership is an important step by itself, Kieran et al (2015) make the point that, in addition to designing policies to ensure that more women own land, focus also needs to be on allowing women to manage and make decisions regarding those lands.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…The rigidity of the statutes and gender roles on farm families is explained by the problem of women's unequal access to agricultural property rights and agricultural education and to the persistent weakness of institutional support to increase Participation and power of women in agricultural households (Istenic, 2015). Kieran, Sproule, Doss, Quisumbing and Kim (2015) report that policy-makers and researchers have largely come to the conclusion that strengthening women's property rights is crucial to poverty reduction and achieving equitable growth. In Ethiopia, according to the 2009 socio-demographic survey data, a female head of household handles an average of 4.39 people and has an average property right of 1.73 hectares against a male head of household who has property rights in Average over 2.20 hectares (Krumar and Quisumbing, 2015).…”
Section: Gender and Land Rightsmentioning
confidence: 99%